Drugs, Brains and Other Subalterns: Public Debate and the New Materialist Politics of Addiction - Fraser, Suzanne; valentine, K.; Ekendahl, M. (Sage Publications, 2018)
© 2018, The Author(s) 2018. Over the last few decades feminists, science and technology studies scholars and others have grappled with how to take materiality into account in understanding social practices, subjectivity and events. One key area for these debates has been drug use and addiction. At the same time, neuroscientific accounts of drug use and addiction have also arisen. This development has attracted criticism as simplistically reinstating material determinism. In this article we draw on 80 interviews with health professionals directly involved in drug-related public policy and service provision in three countries to identify the main ways the neuroscience of addiction (and thus the agency of the brain) is understood. We analyse these understandings using contemporary posthumanist theory to develop new options for conceptualizing matter in public responses to addiction. We close by calling for a new approach to addiction and the brain based on a process model of materiality and public debate.